Computational evaluation of Ca-decorated nanoporous CN monolayers as high capacity and reversible hydrogen storage media. (8th August 2022) - Yong, Yongliang; Hu, Song; Yuan, Xiaobo; Gao, Ruilin; Hou, Qihua; Kuang, Yanmin
Abstract: Developing novel materials with high-capacity and reversible properties for storing hydrogen (H2 ) is crucial for energy treatments. We here investigated comprehensively the H2 storage performance of the Ca-decorated g-CN (Ca@CN) monolayers using first-principles calculations. The Ca atoms can be uniformly decorated into the center of the pores of g-CN monolayers without aggregation. The Ca@CN monolayer has an average H2 adsorption energy of around 0.163–0.228 eV as well as high H2 storage capacity of 10.1 wt%. The stabilities of the H2 adsorption systems are confirmed by high hardness and low electrophilicity. The temperature of desorption is anticipated to be near the room temperature and ideal for fuel cell devices. The thermodynamic analysis along with desorption temperature reveal that the Ca@CN monolayer has promising potentials as reversible and high capacity hydrogen storage materials (HSM), which will motivate experimental efforts to synthesize the high-efficient HSM. Graphical abstract: Image 1 Highlights: H2 storage properties of Ca-decorated-CN monolayer were studied using DFT+D methods. Ca-decorated-CN monolayer is thermodynamically stable enough for Hydrogen storage. Ca-decorated-CN monolayer stores 10.1 wt% H2 with ideal adsorption energies of 0.163–0.228 eV. High hardness and low electrophilicity provides the stabilities of H2 adsorption. Desorption temperature and thermodynamic analysis verify the reversibility of H2 storage.